Advances in Phytochemistry, Textile and Renewable Energy Research for Industrial Growth Proceedings of the International Conference of Phytochemistry, Textile and Renewable Energy for Sustainable development (ICPTRE 2020), August 12-14, Eldoret, Kenya - Nzila, Charles; Oluoch, Nyamwala; Kiprop, Ambrose; Ramkat, Rose; Kosgey, Isaac S. (Taylor & Francis, 2022)
The International Conference on Phytochemistry, Textile, & Renewable Energy Technologies for Sustainable Development (ICPTRE 2020) was hosted by the World bank funded Africa Centre of Excellence in Phytochemicals, Textile and Renewable Energy (ACEII-PTRE) based at Moi University in conjunction with Donghua University, China and the Sino-Africa International Symposium on Textiles and Apparel (SAISTA). The theme of the conference was Advancing Science, Technology and Innovation for Industrial Growth. The research relationships between universities and industry have enabled the two entities to flourish and, in the past, have been credited for accelerated sustainable development and uplifting of millions out poverty. ICPTRE 2020 therefore provided a platform for academic researchers drawn from across the world to meet key industry professionals and actively share knowledge while advancing the role of research in industrial development, particularly, in the developing nations. The conference also provided exhibitors with an opportunity to interact with professionals and showcase their business, products, technologies and equipment. During the course of the conference, industrial exhibitions, research papers and presentations in the fields of phytochemistry, textiles, renewable energy, industry, science, technology, innovations and much more were presented.